Analisis Keamanan Website Kecamatan Cibodas Tangerang Dengan Metode Open Web Application Security Project - Mansen Sagala, Janstipen Roy; Budiarti, Yusnia; Serli, Rosi Kusuma (Jurnal Informatika, 2024)
This research aims to conduct a security analysis on the website kec-cibodas.tangerangkota.go.id using the Open Web Application Security Project (OWASP) methodology. The findings indicate that the OWASP methodology is effective in identifying security vulnerabilities in the web-based application. Several significant results have been uncovered, revealing potential vulnerabilities that could be exploited by malicious actors. The primary findings of this research indicate that OWASP tools remain relevant and reliable as a foundation for website security testing, given the detection of several vulnerabilities. However, it is noted that the domain kec-cibodas.tangerang-kota.go.id is considered relatively secure from potential security threats. This research contributes significantly to understanding and enhancing website security by highlighting existing vulnerabilities and providing recommendations for necessary improvement measures. The results of this study are expected to serve as a basis for developing security policies and more effective preventive measures against potential attacks on the kec.cibodas.go.id website.